Longitudinal trends in university financial performance. (11th May 2004) - Pursglove, Jeff; Simpson, Mike
University financial performance presents a complex set of problems for managers. This research builds on previous work that provided a simple model of financial performance using data found in the public domain, and which yielded six key ratios describing: the nature of a university's business; its academic and operational efficiency; and its research strategy. That model has been improved and its ratios calculated for six English universities from 1994/95 to 2000/01. Trends in these ratios are related to the strategies and the business environment of the universities concerned. The research quantifies the effects of the Research Assessment Exercise (RAE) upon the behaviour of the universities, and shows how the model can be used to explain the current problems faced by the University of Newcastle upon Tyne.